Dr. Bhim Rao Ambedkar’s Views on Social Justice: An Appraisal - Bragta, Sanjeev Kumar (Technium Social Sciences Journal, 2021)
Baba Sahib Bhim Rao Ambedkar views on social justice are the very basis of the Indian Constitution. The social justice means providing equal social opportunities to everyone to develop their personalities, associated with equality and social rights. In every state it becomes important to secure a social order based on justice and creating an equal opportunity available to everyone. Mostly, the people are being treated with discrimination in size, color, caste, religion, race in the society because of they are mostly uneducated and from marginalized sections of the society that creates a social disorder and inequality among them. Hence, the need of the social justice is an inevitable and is the only weapon to prosper the people towards their active participation in the development and mainstream of the society. However, it becomes important to establish an egalitarian social, economic and political order in diverse society like India. It’s in this backdrop the article tries to explore the concept of social justice and Ambedkar view on it. How far Ambedkar’s reflection is visible in Indian Constitution and its relevance in the present times.